Differential phospholipase C‐dependent modulation of TASK and TREK two‐pore domain K+ channels in rat thalamocortical relay neurons. (3rd November 2014) - Bista, Pawan; Pawlowski, Matthias; Cerina, Manuela; Ehling, Petra; Leist, Michael; Meuth, Patrick; Aissaoui, Ania; Borsotto, Marc; Heurteaux, Catherine; Decher, Niels; Pape, Hans‐Christian; Oliver, Dominik; et al.
<x xml:space="preserve">Abstract</x> Key points During the behavioural states of sleep and wakefulness thalamocortical relay neurons fire action potentials in high frequency bursts or tonic sequences, respectively. The modulation of specific K+ channel types, termed TASK and TREK, allows these neurons to switch between the two modes of activity. In this study we show that the signalling lipids phosphatidylinositol 4, 5‐bisphosphate (PIP2) and diacylglycerol (DAG), which are components of their membrane environment, switch on and shut off TREK and TASK channels, respectively. These channel modulations contribute to a better understanding of the molecular basis of the effects of neurotransmitters such as ACh which are released by the brainstem arousal system. The present report introduces PIP2 and DAG as new elements of signal transduction in the thalamus. Abstract The activity of two‐pore domain potassium channels (K2P) regulates the excitability and firing modes of thalamocortical (TC) neurons. In particular, the inhibition of two‐pore domain weakly inwardly rectifying K+ channel (TWIK)‐related acid‐sensitive K+ (TASK) channels and TWIK‐related K+ (TREK) channels, as a consequence of the stimulation of muscarinic ACh receptors (MAChRs) which are coupled to phosphoinositide‐specific phospholipase C (PLCβ), induces a shift from burst to tonic firing. By using a whole cell patch‐clamp approach, the contribution of the membrane‐bound second messenger molecules phosphatidylinositol 4, 5‐bisphosphate (PIP2) and diacylglycerol (DAG) acting downstream of PLCβ was probed. The standing outward current (ISO) was used to monitor the current through TASK and TREK channels in TC neurons. By exploiting different manoeuvres to change the intracellular PIP2 level in TC neurons, we here show that the scavenging of PIP2 (by neomycin) results in an increased muscarinic effect on ISO whereas increased availability of PIP2 (inclusion to the patch pipette; histone‐based carrier) decreased muscarinic signalling. The degree of muscarinic inhibition specifically depends on phosphatidylinositol phosphate (PIP) and PIP2 but no other phospholipids (phosphatidic acid, phosphatidylserine). The use of specific blockers revealed that PIP2 is targeting TREK but not TASK channels. Furthermore, we demonstrate that the inhibition of TASK channels is induced by the application of the DAG analogue 1‐oleoyl‐2‐acetyl‐sn‐glycerol (OAG). Under current clamp conditions the activation of MAChRs and PLCβ as well as the application of OAG resulted in membrane depolarization, while PIP2 application via histone carrier induced a hyperpolarization. These results demonstrate a differential role of PIP2 and DAG in K2P channel modulation in native neurons which allows a fine‐tuned inhibition of TREK (via PIP2 depletion) and TASK (via DAG) channels following MAChR stimulation.